C++ builder 5 developer's guide - Hollingworth, Jarrod (SAMS, 2001)
C++Builder 5 Developer's Guide is a completely new book authored by insiders of the C++Builder development community. You will learn advanced debugging techniques using CodeGuard, master multi-tier distributed applications with MIDAS 3, discover the latest in multi-media techniques with OpenGL, DirectX, and others, master memory management, learn how to build a chat system with TCP/IP, and more. XML, HTML, CORBA, VisiBroker, ActiveX, and COM+ Server are new features covered by this new edition.